2010
DOI: 10.1007/978-3-642-16419-4_30
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Knowledge: Ethics and the Importance of Trust

Abstract: Abstract. The aim of this paper is to grasp the ethical dilemmas that arise into organizational knowledge and the importance of trust for diminishing these dilemmas. Therefore, it focuses three key issues: knowledge management (concept; and, schools of thought); knowledge flowing models versus ethics (mental models; the Socialization, Externalization, Combination, Internalization (SECI) model; and, Fiske's relational model); and finally, the importance of trust as a possible answer. Plus, this paper suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, according to Weber (1905) [1], the highest form of the moral obligation of an individual is to perform his/her duty with dedication. Moreover, recent scholarship suggests that creating new knowledge and sharing knowledge to enhance organizations' competencies are employees' indispensable moral obligations (da Costa et al, 2010;Du Plessis et al, 2006;Rechberg and Syed, 2013). As ethics is the central focus of ethical Ethical leadership and learning leadership (Brown et al, 2005), ethical leaders are likely to engage in their work roles and learning behaviors with dedication.…”
Section: Ethical Leadership and Exploitative Learning And Explorative...mentioning
confidence: 99%
“…For example, according to Weber (1905) [1], the highest form of the moral obligation of an individual is to perform his/her duty with dedication. Moreover, recent scholarship suggests that creating new knowledge and sharing knowledge to enhance organizations' competencies are employees' indispensable moral obligations (da Costa et al, 2010;Du Plessis et al, 2006;Rechberg and Syed, 2013). As ethics is the central focus of ethical Ethical leadership and learning leadership (Brown et al, 2005), ethical leaders are likely to engage in their work roles and learning behaviors with dedication.…”
Section: Ethical Leadership and Exploitative Learning And Explorative...mentioning
confidence: 99%
“…The problem is that individuals' interests are not always considered in the benefits that organisations reap from their knowledge, which can lead to the reluctance to share knowledge and free riding (Britz et al, 2006;Da Costa et al, 2010). Free riding can result where individuals' knowledge is praised as a public good (Wang and Noe, 2010).…”
Section: The Conflict Of Knowledge Ownershipmentioning
confidence: 99%
“…In that case, extrinsic motivators may be able to mitigate this behavior only if the rewards and reciprocal relationships match the knower’s interest. Indeed, da Costa et al (2010) found that where individual values differ from that of the organization, knowledge sharing may not be supported. In her study to identify rewards that encourage knowledge sharing, Šajeva (2014, p. 133) found that “a sense of belonging and sharing common values, a sense of achievement and success, a sense of competence, a sense of usefulness, a sense of respect and recognition, and a sense of trust are acknowledged to be important for fostering knowledge sharing among employees.” These needs may be fulfilled by both intrinsic and extrinsic motivators and may also combat amotivation.…”
Section: Discussionmentioning
confidence: 99%